The functional role of hemojuvelin in acute ischemic stroke - Young, Guang-Huar (J Cereb Blood Flow Metab, 2019)
Our study aimed to establish the role of hemojuvelin (HJV) in acute ischemic stroke (AIS). We performed immunohistochemistry for HJV expression in human brain tissues from 10 AIS and 2 non-stroke autopsy subjects. Plasma HJV was measured in 112 AIS patients within 48 h after stroke. The results showed significantly increased HJV expression in brain tissues from AIS patients compare to non-stroke subjects. After adjusting for clinical variables, plasma levels of HJV within 48 h after stroke were an independent predictor of poor functional outcome three months post-stroke (OR:1.78, 95% CI: 1.03–3.07; P = 0.038). In basic part, Western blotting showed that HJV expression in mice brains was apparent at 3 h after middle cerebral artery occlusion (MCAO), and increased significantly at 72 h. In cultured cortical neurons, expression of HJV protein increased remarkably 24 h after oxygen glucose deprivation (OGD), and small interfering RNAs (siHJV) transfected OGD neurons had a lower apoptotic rate. Importantly, 72 h post-MCAO, HJV knockout mice had significantly smaller infarcts and less expression of cleaved caspase-3 protein compared with wild-type mice. In summary, HJV participates in the mechanisms of post-stroke neuronal injury, and that plasma HJV levels can be a potential early outcome indicator for AIS patients.